The 2009 Frank Stinchfield Award: “Hip Squeaking”: A Biomechanical Study of Ceramic-on-ceramic Bearing Surfaces - Chevillotte, Christophe (Springer-Verlag, 2009)
We designed and implemented an in vitro bench test to simulate and identify potential biomechanical causes for hip squeaking with alumina ceramic-on-ceramic bearing surfaces. All bearings were third-generation alumina ceramic with a 32-mm head coupled with a 56-mm acetabular component with a 32-mm ceramic insert. Conditions for testing were normal gait, high load, stripe wear, stripe wear in extreme load, metal transfer, edge wear with extreme load, and microfracture. Each condition was tested two times in dry conditions and two times in a lubricated condition with 25% bovine serum. Squeaking was reproduced in all dry conditions. It occurred quickly with high load, stripe wear, or metal transfer. Once squeaking occurred, it did not stop. Squeaking disappeared for all conditions when a small amount of lubricant was introduced. In lubricated conditions, squeaking was only reproduced for the material transfer condition. Our observations suggest squeaking is a problem of ceramic-ceramic lubrication and that this noise occurs when the film fluid between two surfaces is disrupted. Material (metal) transfer was the only condition that led to squeaking in a lubricated situation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11999-009-0911-x) contains supplementary material, which is available to authorized users.